The Utilization of Mobile-Based GeoGebra Applications for Elementary School Educators - Sekreningsih Nita; Erny Untari; Indra Puji Astuti; Eka Resty Novieta Sari; Kelik Sussolaikah (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
In the current Generation-Z Era, the use of digital technology in learning, especially mathematics in elementary schools, is increasingly important to increase student effectiveness and engagement. GeoGebra Mobile, as a dynamic mathematics application, offers interactive visualizations that can help students understand abstract concepts more concretely. This study discusses the use of mobile-based GeoGebra in mathematics learning at the Bancong Elementary School level, Madiun Regency, which includes materials on plane figures, fractions, number lines, and simple Cartesian coordinates. Meanwhile, the method used in this study is a literature review by examining various sources such as journals, books, and relevant research reports related to the use of the GeoGebra Mobile application in elementary mathematics learning. Furthermore, the researcher conducted analysis and scoring by grouping several findings based on benefits, implementation, as well as challenges and solutions. The final results of the study show that the GeoGebra Mobile application can help in visualizing abstract concepts, making it easier to understand concepts and being skilled in solving basic mathematical problems with a score of 90.00 (very good), GeoGebra as an interactive and innovative mathematics learning score of 85.15 (very good), with GeoGebra can motivate students to learn score of 88.50. In addition, GeoGebra also supports students in independent learning score of 80.50 (good) and can facilitate authentic assessment with a score of 80.10 (good). Although there are several technical challenges, practical solutions can be implemented so that the use of the GeoGebra Mobile application remains optimal. The conclusion is that the use of the GeoGebra Mobile application is in line with the characteristics of today's students (gen-z) who are familiar with digital devices.